Hubungan Perilaku Hidup Bersih Dan Sehat Ibu Dengan Kejadian Diare Pada Usia 3 Bulan 2 Tahun Di Desa Pulosari Kecamatan Kebakkramat Kabupaten Karanganyar - Kusumasari, Ratna Diani, dr. Burhanudin Ichsan, M.Med,Ed.,M.Kes, dr. Erika Diana Risanti (2015)
Background. The diarrhea on infants and children possibly causing negative impact specifically the children growth process that lead to decrease the life quality of children. The environment and behavior are the of diarrhea. Objective. To determine existing relations between hygienic and healthy mother behavior with diarrhea at age 3 months until 2 years children in Pulosari Kebakkramat Karanganyar. Method. The research are using the observational method with the cross sectional approach. The research conducted in Pulosari Kebakkramat Karanganyar in January 15, 2015. The sample are 38 respondent, obtained by using the cluster random sampling. The research variables the hygienic and healthy mother behavior and the diarrhea incident on children. The hygienic and healthy mother behavior obtained with healthy life and health behavior of housewifery questionnaire. The diarrhea incident data obtained by diarrhea questionnaire. The statistical test using the chi square test. Results. The population of mother with hygienic life and healthy behavior on bad category 13 (34,2%)), while the mother with hygienic life and healthy behavior on good category 25 (65,8%). Further, the data are analyzed with chi square and the results is p with the amount 0.001 (p<0,05) which means the correlations between the hygienic life and healthy behavior mother on diarrhea incident at age 3 months to 2 years in Pulosari Kebakkramat Karanganyar are exist Conclusion. The research conclude that the significant correlations between hygienic and healthy mother behavior with diarrhea genesis at age 3 months to 2 years in Pulosari of Kebakkramat Karanganyar are exist.